L-cystathionine protects against oxidative stress and DNA damage induced by oxidized low-density lipoprotein in THP-1-derived macrophages - Peng, Hanlin; Zhu, Mingzhu; Kong, Wei; Tang, Chaoshu; Du, Junbao; Huang, Yaqian; Jin, Hongfang (Frontiers in Pharmacology, 2023)
Oxidative stress in monocyte-derived macrophages is a significant pathophysiological process in atherosclerosis. L-cystathionine (L-Cth) acts as a scavenger for oxygen free radicals. However, the impact of L-Cth on macrophage oxidative stress during atherogenesis has remained unclear. This study aimed to investigate whether L-Cth affects oxidative stress in THP-1-derived macrophages and its subsequent effects on DNA damage and cell apoptosis. We established a cellular model of oxLDL-stimulated macrophages. The results demonstrated that oxLDL significantly increased the content of superoxide anion and H2O2, the expression of iNOS protein, and NO production in macrophages, compared to the control group. Conversely, oxLDL decreased the activity of antioxidants GSH-Px, SOD, and CAT, and downregulated the protein expressions of SOD1 and SOD2 in macrophages. However, treatment with L-Cth reduced the levels of superoxide anion, H2O2, and NO, as well as the protein expression of iNOS induced by oxLDL, compared to the oxLDL group. Moreover, L-Cth treatment significantly enhanced GSH-Px, SOD, and CAT activity, and upregulated the expressions of SOD1 and SOD2 protein in macrophages treated with oxLDL. Furthermore, both L-Cth supplementation and activation of endogenous L-Cth production suppressed DNA damage and cell apoptosis in oxLDL-injuried macrophages, whereas inhibition of endogenous L-Cth exacerbated the deleterious effects of oxLDL. These findings suggest that L-Cth exerts a pronounced inhibitory effect on the oxidative stress, subsequent DNA damage and cell apoptosis in oxLDL-stimulated THP-1 monocytes. This study deepens our understanding of the pathogenesis of macrophage-related cardiovascular pathology.